Prevalence of Post Stroke Depression in Male and Female Patients Visiting A Rural Hospital Out Patient Department - Chakraborty, Suddhendu; Basu, Rajkumari; Jana, Amlan Kusum; Banerjee, Monideepa; Sanyal, Debasish (International Journal of Innovative Research in Medical Science, 2016)
Stroke is a clinical entity of immense importance considering both psychiatric and psychological aspects of any social being. This study is unique because it is being undertaken in patients attending neuropsychiatry outpatient department in a rural hospital unlike most of the studies that have been conducted in an urban setting. A sample size of 50 male and 50 female has been chosen to statistically correlate the concerned variables. In this study it was found depression was more associated with adult male post stroke patients belonging to the age group of 51 to 60 years compared to the females as obtained by Post Stroke Depression Rating Scales (PSDRS). It interesting to note that in the present study finding the male patients of both the age groups were found to suffer more from somatic symptoms compared to the females.